Synthesis of some novel 2-(3-cyano -6-(thiophen- 2-yl)-4,4′- bipyridin-2- yloxy)acetohydrazide derivatives: assessment of their cytotoxic activity - Hossa F. Al Shareef (BMC Chemistry, 2020)
Abstract A new series of pyrazole, bipyridine, N-amide derivatives and Schiff bases was synthesized using compound 2-(3-cyano-6- (thiophen-2-yl)-4,4′- bipyridin-2-yloxy) acetohydrazide (3) as a starting material. The compounds structures were confirmed depending on the spectroscopic methods and elemental analysis. Also, the compounds were evaluated as anticancer agents by the compounds screened towards adenocarcinoma breast cancer cell line (MCF-7). The compounds showed a promising cytotoxic effect against human breast cancer cells. Compound 7c showed the most effective activity compared to other compounds with (IC50 = 0.6 ± 0.01 μg mL−1) in comparison with the reference drug doxorubicin (IC50 = 1.6 ± 0.02 μg mL−1). While compound 3 is closely active with doxorubicin. Also compounds 2, 4, 6, 7a, 7b and 7d showed noticeable cytotoxic effect. Early and late apoptotic cells were detected using Acridine orange/Ethidium bromide staining technique. The results of biologically screening of the tested compounds give an idea about the importance in the compounds acting against breast cancer and may lead to the discovery of a potent anticancer agent.